(untitled) (Research, Society and Development, 2021)
This article aimed to understand whether playing favors the inclusion of students diagnosed with Autistic Spectrum Disorder (ASD) and whether it can be used as a strategy for school inclusion. To elucidate the issue, a qualitative and descriptive case study was developed with education professionals from a public school in the city of Governador Valadares, Minas Gerais. The questionnaire applied via the Google Forms was used as a research tool. According to the data obtained, it was observed that in the respondents’ perception, playing favors the inclusion of students diagnosed with ASD and can be used as a strategy for this inclusion, mainly because it promotes the global development of children, since, in their view provides learning, interaction and respect for difference. Respondents also pointed out the importance of strengthening the family-school relationship for more effective work with children and the need for continued formation to support inclusion work. The work shows how playing is increasingly present in schools and its importance in the inclusion and autonomy of students.